Reaping the Whirlwind: Reply to Garth Stevens, Gillian Eagle, Margarita Kahn, and Donna Orange. Issue 3 (4th May 2018) - Straker, Gillian
Abstract : Drawing on the work of Žižek (1992) on the neighbor, this paper grapples with Orange's ethical challenges in this regard. Continuing a focus on the complexity of extending a hand to the Other, the paper then address Kahn's ideas concerning how one pole of a binary defines itself through the Other, and I speak to the issue of victims and rescuers. The resistance of the erstwhile oppressed to being defined by the Other is taken up in Eagle's paper. Eagle discusses the perils of reflection and interpretation when at the receiving end of the jouissance of embodied and enacted hatred. In this reply I elaborate these thoughts, and then move to discuss Stevens's paper, which offers thoughts on how to respond constructively to this jouissance so as not to make a bad situation worse.